2009
DOI: 10.1603/022.038.0346
|View full text |Cite
|
Sign up to set email alerts
|

Deleterious Effects of Uv-B Radiation on Herbivorous Spider Mites: They Can Avoid It by Remaining on Lower Leaf Surfaces

Abstract: The herbivorous spider mite Tetranychus urticae usually remains on the lower leaf surfaces of its host plants. Although terrestrial animals are generally thought to be well protected from damage because of UV radiation, insect herbivory frequently increases when solar UV-B (280-315 nm) radiation is attenuated. As UV transmission through leaves is generally low because of the accumulation of compounds that act as selective sunscreens (e.g., phenolics), we hypothesized that T. urticae avoids solar UV-B radiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
92
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(95 citation statements)
references
References 47 publications
3
92
0
Order By: Relevance
“…Artificial UV-B irradiation was reported to reduce the incidence of fungal diseases, such as strawberry powdery mildew (Kanto et al, 2009(Kanto et al, , 2014, rose powdery mildew (Kobayashi et al, 2013), and eggplant leaf mold caused by Mycovellosiella nattrassii (Oka et al, 2011). Moreover, it was reported that UV-B irradiation hindered the survival and reproduction of the herbivorous spider mite Tetranychus urticae (Murata and Osakabe, 2013;Ohtsuka and Osakabe, 2009). The mortalities of adult females, larvae, and eggs of T. urticae were proportional to the cumulative UV-B irradiance to which they were exposed (Murata and Osakabe, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Artificial UV-B irradiation was reported to reduce the incidence of fungal diseases, such as strawberry powdery mildew (Kanto et al, 2009(Kanto et al, , 2014, rose powdery mildew (Kobayashi et al, 2013), and eggplant leaf mold caused by Mycovellosiella nattrassii (Oka et al, 2011). Moreover, it was reported that UV-B irradiation hindered the survival and reproduction of the herbivorous spider mite Tetranychus urticae (Murata and Osakabe, 2013;Ohtsuka and Osakabe, 2009). The mortalities of adult females, larvae, and eggs of T. urticae were proportional to the cumulative UV-B irradiance to which they were exposed (Murata and Osakabe, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…While cited reports point to the reaction of stressed plants, there could be a direct light influence on herbivores. For instance, UVA and UVB radiation have an effect on mite survival, reproduction, and spatial distribution on host-plants (Ohtsuka and Osakabe 2009;Sakai and Osakabe 2010). It was also determined that visible light treatment after UVB treatment caused photoreactivation of adult females, resulting in the increased survival recovery of T. urticae and Tyrophagus putrescentiae (Santos 2005), and effects on the egg hatchability of T. urticae as well as predatory mite (Koveos et al 2017;Murata and Osakabe 2014).…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies demonstrated that solar UVB radiation also largely affected the behavior of spider mites (Ohtsuka and Osakabe 2009;Sakai and Osakabe 2010) and phytoseiid mites (Onzo et al 2010), and possibly restricted their foliar surface availability. Since Phytoseius nipponicus Ehara was the phytoseiid mite species commonly observed on VEP (Sudo et al 2010) and that preyed upon B. obovatus eggs (M. Sudo, unpublished data), it is likely that P. nipponicus was also vulnerable to UVB radiation as well as other phytoseiid mites.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the effects of solar UV radiation on survival and spatial distribution between the upper and lower leaf surfaces have been investigated in herbivorous spider mites (Ohtsuka and Osakabe 2009;Suzuki et al 2009;Sakai and Osakabe 2010) and predaceous phytoseiid mites (Onzo et al 2010). 'Reverse gravity' experienced by inhabitants on the upper or lower leaf surfaces was also suggested to affect the distribution of a spider mite, i.e., mites preferred the leaf surface facing downward, regardless whether this was the morphological adaxial or abaxial side (Li and Margolies 1991).…”
Section: Introductionmentioning
confidence: 99%